Mapping the journey: Supporting transition from preschool to primary school for children on the autism spectrum in Ireland. A mixed methods exploratory study. - KENNEDY-KILLIAN, SUSAN ANN (Trinity College Dublin. School of Education. Discipline of Education, 2019)
Transition to primary school is reported as being a key moment in a child's life (Dockett & Perry 2001), however, for children on the autism spectrum it can be challenging, as difficulty coping with change is reported as being a key feature of autism (APA, 2013). This research, which has been funded by Middletown Centre for Autism, explores experiences of supporting transition from preschool to primary school for children on the autism spectrum in Ireland. The study explores what transition from preschool to primary school for children with autism in Ireland looks like from the perspective of parents/guardians, preschool staff, primary school staff, and clinicians so as to research the following key questions: What is a successful transition from preschool to primary school for a child on the autism spectrum in Ireland? What supports a successful transition from preschool to primary school for a child on the autism spectrum in Ireland? What hinders a successful transition from preschool to primary school for a child on the autism spectrum in Ireland? A mixed methods, exploratory approach has been used, incorporating qualitative and quantitative research. Findings from the study indicate that successful transition from preschool to primary school for a child on the autism spectrum in Ireland involves a process that occurs over time, whereby a child moves from a preschool that is appropriate to his/her needs to a primary school that is appropriate to his/her needs. The transition involves the child being content and happy at school, engaging in successful horizontal transitions through the school day, progressing developmentally in emotional, social, behavioural, academic, communicative, and independent living and self-care skills, and receiving support for areas of developmental need. Factors identified in the study as supporting successful transition from preschool to primary school for a child with autism in Ireland include: i. timely provision of critical core supports, described in the study as the big machinery of support, which involve timely assessment and diagnosis, clinical support, appropriate educational placement with one-to-one/SNA support and primary school staff being trained and experienced in ASD, promotion of positive relationships and communication, and education and transition planning, and ii. incorporation of transition support processes into the school day, described in the study as the engines that power the big machinery of support, which include transition support strategies, materials, and interactions. It was identified in the study that support is required for both the vertical transition to school and for the frequent horizontal transitions that occur throughout the school day. In addition, it was found that both the provision of critical core supports and the incorporation into the school day of transition support processes involve provision of support for the child and also provision of support for those working with the child; parents/guardians, preschool staff, primary school staff, and clinicians. Factors that were identified as supporting transition to school were found not only to be helpful but to be critical for successful transition to school, and, consequently, it was found that lack of provision of those critical supports could result in barriers to successful transition from preschool to primary school for a child on the autism spectrum in Ireland.
APPROVED
Keywords: Autism; Transition; Preschool; Primary School; Ireland